Integrating Technology Adoption Models Into Implementation Science Methodologies: A Mixed-Methods Preimplementation Study. - Gallant, Natasha L; Hadjistavropoulos, Thomas; Stopyn, Rhonda J N; Feere, Emma K (Gerontologist, 2023)
Background and Objectives Sustainable implementation of patient-oriented technologies in health care settings is challenging. Preimplementation studies guided by the Consolidated Framework for Implementation Research (CFIR) can provide opportunities to address barriers and leverage facilitators that can maximize the likelihood of successful implementation. When looking to implement patient-oriented technologies, preimplementation studies may also benefit from guidance from a conceptual framework specific to technology adoption such as the Unified Theory of Acceptance and Use of Technology. This study was, therefore, aimed at identifying determinants for the successful implementation of a patient-oriented technology (i.e. automated pain behavior monitoring [APBM] system) within a health care setting (i.e. long-term care [LTC] facility). Research Design and Methods Using a mixed-methods study design, 164 LTC nurses completed a set of questionnaires and 68 LTC staff participated in individual interviews involving their perceptions of an APBM system in LTC environments. Quantitative data were analyzed using a series of mediation analyses and narrative responses were examined using directed content analysis. Results Performance expectancy and effort expectancy partially and fully mediated the influence of implementation, readiness for organizational change, and technology readiness constructs on behavioral intentions to use the APBM system in LTC environments. Findings from the qualitative portion of this study provide guidance for the development of an intervention that is grounded in the CFIR. Discussion and Implications Based on our results, we offer recommendations for the implementation of patient-oriented technologies in health care settings.